Wednesday

July 30, 2014

July 30, 2014

Posted by **hhfo** on Tuesday, July 26, 2011 at 7:30am.

Prove the following;

(tan^2x)(cos^2x)

=

(sec^2x - 1)(1-sin^4x) ÷ (1+sin^2x)

- Math -
**Reiny**, Tuesday, July 26, 2011 at 8:09amremember :

1 + tan^2x = sec^x and 1-sin^2x = cos^2 from the Pythagorean identities, so

RS = tan^2x(1-sin^2x)(1+sin^2)/(1+sin^2x)

= tan^2x(1-sin^2x)

= tan^2x cos^2x

= LS

- Math -
**hhfo**, Tuesday, July 26, 2011 at 8:26amOkay I was confused about what to do with the power of 4..

Thank You!!

**Related Questions**

Trigonometry desperate help, clueless girl here - 2. solve cos 2x-3sin x cos 2x...

Trigonometry - 1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two ...

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

trigonometry hlp me - 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin y...

Trigonometry - Prove the following trigonometric identities. please give a ...

precalculus - For each of the following determine whether or not it is an ...

Trig Identities - Proving identities: 1) 1+ 1/tan^2x = 1/sin^2x 2) 2sin^2 x-1 = ...

Trigonometry - Verify/Solve the identities. 1.) SIN^1/2 X COS X-SIN^5/2 X COS X ...

Trigonometry - Verify the identities algebraically. 1.) TAN^5 X= TAN³X SEC²X-TAN...

MATH - Hi, I really need help with these questions. I did some of them halfway, ...